Atractylenolide I prevents acute liver failure in mouse by regulating M1 macrophage polarization - Hui Zhang; Min Gao; Haiyan Wang; Junfeng Zhang; Lin Wang; Guanjun Dong; Qun Ma; Chunxia Li; Jun Dai; Zhihua Li; Fenglian Yan; Huabao Xiong (Scientific Reports)
Abstract Acute liver failure (ALF) is a life-threatening clinical syndrome with a substantial risk of mortality. A murine model of lipopolysaccharide (LPS)- and D-galactosamine (D-GalN)-induced ALF is widely used to investigate the underlying mechanisms and potential therapeutic drugs for human liver failure. Atractylenolide I (ATR-I) is an active component of the Atractylodes macrocephala rhizome and possesses various pharmacological activities, including anti-tumor, anti-inflammatory, and anti-oxidant properties. Given the key role of oxidative stress and inflammation in ALF pathogenesis, this study investigates the protective effects of ATR-I on LPS/D-GalN-induced ALF in mice. The results suggest that ATR-I pretreatment significantly ameliorates ALF, as evidenced by decreased serum aminotransferase levels and prolonged mice survival. Additionally, ATR-I pretreatment inhibits oxidative stress. Furthermore, the ATR-I pretreatment markedly suppresses M1 macrophage activation in hepatic mononuclear cells. In vitro experiments with bone marrow-derived macrophages indicate that ATR-I regulates macrophage polarization through the mitogen-activated protein kinase (MAPK) and interferon regulatory factor (IRF) signaling pathways. Collectively, ATR-I pretreatment protects mice from LPS/D-GalN-induced ALF partially by regulating M1 macrophage polarization.